2019
DOI: 10.22159/ijap.2019.v11s1.17138
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Silver Diamine Fluoride and Propolis Fluoride Varnish Application on Dentin Within 60 Days

Abstract: Objective: This study sought to analyze the effectiveness of silver diamine fluoride (SDF) and propolis fluoride (PPF) varnish application on dentinwithin 60 days.Methods: We divided 60 blocks (4 mm × 4 mm × 2 mm) of human permanent teeth dentin specimens into six time-based groups: 0 days, 1 day, 7 days,14 days, 30 days, and 60 days. We then applied 20 μL SDF and PPF varnish to the specimens’ occlusal surfaces. For the fluoride test, all specimenswere submerged in deionized water, while for the flavonoid test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This result varies from the in vivo study done by SG Shah et al in 2014, [30] where significant fluoride content of enamel was found in SDF when compared to Fluoride varnish and APF gel. This research also varied from a study done by Soekanto SA, Dayanara P, Daviq H, Sarwono AT, Sahlan M in 2019, [31] where SDF released more fluoride ions than PPF from dentin within 60 days. This research varied from a study done by Widianti TA, Bahar A, Maharani DA, Tumen E.C, Yavuz I.…”
Section: Discussionmentioning
confidence: 99%
“…This result varies from the in vivo study done by SG Shah et al in 2014, [30] where significant fluoride content of enamel was found in SDF when compared to Fluoride varnish and APF gel. This research also varied from a study done by Soekanto SA, Dayanara P, Daviq H, Sarwono AT, Sahlan M in 2019, [31] where SDF released more fluoride ions than PPF from dentin within 60 days. This research varied from a study done by Widianti TA, Bahar A, Maharani DA, Tumen E.C, Yavuz I.…”
Section: Discussionmentioning
confidence: 99%